2015
DOI: 10.1093/molbev/msv011
|View full text |Cite
|
Sign up to set email alerts
|

Functional Organization of the Genome May Shape the Species Boundary in the House Mouse

Abstract: Genomic features such as rate of recombination and differentiation have been suggested to play a role in species divergence. However, the relationship of these phenomena to functional organization of the genome in the context of reproductive isolation remains unexplored. Here, we examine genomic characteristics of the species boundaries between two house mouse subspecies (Mus musculus musculus/M. m. domesticus). These taxa form a narrow semipermeable zone of secondary contact across Central Europe. Due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 73 publications
(105 reference statements)
6
93
4
Order By: Relevance
“…In manakins (Parchman et al, ) and lycaenid butterflies (Gompert, Lucas, et al, ), loci with non‐neutral introgression also showed elevated differentiation in parental populations compared to neutral markers. In the house mouse hybrid zone, Janoušek et al () also observed higher differentiation for markers with reduced introgression, but contrary to our findings, loci with increased introgression showed lower differentiation compared to neutral markers. These results are consistent with the hypothesis that reproductive isolation arises as a by‐product of selection in allopatry, although we recognize that locus‐specific differentiation and introgression are determined by the complex interaction of many factors and that disentangling the effects of selection from other processes can be challenging (Beaumont & Balding, ; Gompert, Parchman, & Buerkle, ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In manakins (Parchman et al, ) and lycaenid butterflies (Gompert, Lucas, et al, ), loci with non‐neutral introgression also showed elevated differentiation in parental populations compared to neutral markers. In the house mouse hybrid zone, Janoušek et al () also observed higher differentiation for markers with reduced introgression, but contrary to our findings, loci with increased introgression showed lower differentiation compared to neutral markers. These results are consistent with the hypothesis that reproductive isolation arises as a by‐product of selection in allopatry, although we recognize that locus‐specific differentiation and introgression are determined by the complex interaction of many factors and that disentangling the effects of selection from other processes can be challenging (Beaumont & Balding, ; Gompert, Parchman, & Buerkle, ).…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, we observed neutral and increased introgression for markers with very high, moderate and no differentiation (i.e., from F ST = 0 to F ST = 1) (Figure b). These observations are similar to those in other hybrid zones (e.g., Janoušek et al, , Schield et al, ) and are likely a reflection of the complexity of the interaction between selection, drift and recombination and suggest that these forces vary across the genome. Despite the mechanism of divergence, this also demonstrates that high differentiation in allopatry is not a perfect predictor for reproductive isolation.…”
Section: Discussionsupporting
confidence: 86%
“…On the one hand, genome reshuffling influences recombination landscapes. On the other hand, gene incompatibilities, reduced introgression, and higher differentiation are often associated with genomic regions with reduced recombination [Geraldes et al, 2011;Seehausen et al, 2014;Janoušek et al, 2015]. Speciation genes have been described mostly in Drosophila , including, for instance, Odysseus-site homeobox (OdsH) [Ting et al, 1998], JYalpha [Masly et al, 2006], and Overdrive (Ovd) genes [Phadnis and Orr, 2009].…”
Section: Chromosomal Rearrangements As Recombination Modifiersmentioning
confidence: 99%
“…This dramatic difference in the localization of hotspots and their evolutionary dynamics has important evolutionary consequences for genome structure and base composition, for linkage disequilibrium (LD) levels along the genome, as well as for introgression patterns in naturally occurring hybrids (Fullerton et al, 2001; McVean et al, 2004; Duret and Galtier, 2009; Janoušek et al, 2015). It is therefore important to establish the generality of these two mechanisms and characterize their distribution across species.…”
Section: Introductionmentioning
confidence: 99%